A global database of measured values of Li/Mg, Mg/Ca, Sr/Ca, Ba/Ca, U/Ca and Sr-U for coral and coralline algae paleoenvironment calibrations - Thomas J Williams; Christopher D Standish; Philippe Archambault; Jasmin A Godbold; Martin Solan; Orestis Katsamenis; Philip Basford; Gavin L Foster (PANGAEA, 2023)
Calcifying marine organisms provide a valuable means to access high-resolution historical records of the marine environment captured within their skeletal geochemistry. These records are essential for comprehending the effects of human-induced climate change and reducing uncertainties in future projections. Integrating investigations across various taxa, depths, and geographic locations can help identify universal environmental proxies and serve as a basis for targeted studies in the future. Here, we provide a comprehensive georeferenced database of measured values of Li/Mg, Mg/Ca, Sr/Ca, Ba/Ca, U/Ca and Sr-U in coral and coralline algae compiled from the scientific literature (1950-2021; http://www.webofknowledge.com, accessed 2022-09-30) for the purpose of interrogating and refining global, mineralogy specific and/or taxon-specific proxies for seawater temperature and barium. We include metadata relating to the source, timing and location of each study, the methodology used, and environmental and experimental information. The dataset presents an opportunity to quantify uncertainty and test the robustness of trace and minor element proxies for past environmental conditions, of which will be of value within the fields of geochemistry, ecology, climate, and palaeobiology. Full methodology and additional information provided in Williams et al. (2024).